Intraoperative hemorrhage as a complication of cesarean myomectomy: Analysis of risk factors - Sparić Radmila (Vojnosanitetski Pregled)
Background/Aim. Cesarean myomectomy is a controversial issue. It was considered relatively contraindicated for many years due to increased risk of intraoperative hemorrhage. Recent studies showed that cesarean myomectomy in some women may not be associated with increased morbidity. The aim of the study was to determine the causes and risk factors for intraoperative hemorrhage in patients subjected to cesarean myomectomy. Methods. This retrospective study included women subjected to cesarean myomectomy, divided into the study group of 36 patients in whom intraoperative hemorrhage was registered, and the control group of 66 patients in whom it was absent. The following parameters were analyzed: age, parity, gestational age of delivery, indications, type and duration of cesarean section, surgeon's experience, type, localization, size and number of myomas, number of incisions on uterus and neonatal birth weight. Results. There was a significant difference between the groups in terms of the type and size of myomas (p = 0.007 and p = 0.000, respectively) and duration of the surgery (p = 0.000). The size of the defect resulting from myoma enucleation and speed of suturing it have significant influence on the occurrence of intraoperative hemorrhage. In our study, operation on the patients of the study group lasted 14.53 minutes longer and their myomas were 39 mm bigger compared to the controls, with no difference in surgical experience of the obstetricians (p = 0.111). Conclusion. Cesarean myomectomy is associated with an increased risk of hemorrhage. Therefore, it would be advisable to discuss the hemorrhage and transfusion risks with patients with large multiple and intramural myomas before making decision to perform cesarean myomectomy. Those who perform cesarean myomectomy should be prepared to manage intraoperative hemorrhage during surgery in cases they encounter it.